GE_GERICHTE P/5964/2022 vom 28. November 2023 - GE Cour de justice (2023)
PRESCRIPTION;FIXATION DE LA PEINE;AGGRAVATION DE LA PEINE;DROITS DE DOUANE;AMENDE | LD.118; LTVA.96.al1; LAlc.54.al2; LD.124; LD.7